The Relationship between Geography Access and Utilization of Basic Emergency Neonatal Obstetric Services (PONED) in Hamparan Perak Health Center, Deli Serdang Regency in 2018 - Winda Novita; Destanul Aulia; Juanita Juanita (Budapest International Research and Critics University, 2020)
Every pregnancy and childbirth is a risky event, therefore every pregnant and childbirth woman must be as close as possible to basic emergency obstetric services. Health service units that are close and affordable to the community Community Health Centreare expected to be able to provide basic emergency neonatal obstetric services. Deli Serdang Regency has a high number of maternal mortality rates (AKI) and there are still cases of maternal deaths due to delays in handling due to geographical factors which is one of the causes of the low utilization of PONED (Pelayanan Obstetri Neonatal Emergency Dasar) Community Health Centre. The study aims to analyze the relationship between geographic access and the use of PONED in Hamparan Perak Health Center, Deli Serdang Regency.This type of research is an explanatory survey with cross sectional approach. The study was conducted in the working area of the Hamparan Perak Health Center with a sample of 100 pregnant, childbirth and postpartum women obtained using the proportional random sampling method. The independent variable in the study is geographic access. The dependent variable in research is the use of PONED. Data obtained using a questionnaire. Data analysis was performed using the chi-square test. The results showed a significant relationship between geographic access and the use of PONED (OR = 9,615; 95% CI = 2,974 to 31,088; p = 0.001). Pregnant, childbirth and childbirth mothers who have an assessment of good geographical access will use the PONED Community Health Centre.